Changes in the climatic water budget of an intermittent river in the Brazilian semiarid: trends in cyclical processes and their relation to teleconnection patterns - da Silva, Thieres George Freire; Rocha, Ana Karlla Penna; de Lucas, Alanderson Firmino; de Souza, Luciana Sandra Bastos; Montenegro, Abelardo Antônio de Assunção; de Souza, Werônica Meira; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; de Souza, Carlos André Alves; Salvador, Kaique Renan da Silva; de Carvalho, Ailton Alves; Araújo Júnior, George do Nascimento (Springer Nature, 2025)
Oceanic-atmospheric phenomena can change the patterns of rainfall (R) and potential evapotranspiration (ET0) and, therefore, the water availability of a location, resulting in significant effects on agricultural activity. This study evaluated the trend of the climatic water budget (W) of a river basin in the Brazilian semiarid region, the Pajeú river basin, as a function of variations in R and ET0 resulting from changes in climate patterns and atmospheric circulation systems. For this, data series of 27 rain gauge and 8 complete weather stations with different time intervals were used (i.e., a maximum range of 1912 to 2019, 108 years). Data from 8 complete weather stations were used to estimate ET0, and to calibrate and validate methods for estimating incident solar radiation (Rs) and ET0, aiming to fill in gaps in the data series. Seasonal and cyclical trends for R, ET0 and W were evaluated on ten timescales, using the Mann–Kendall test, Sen Slope test, Pettitt test and the Seasonal Trend decomposition using Loess. The timescales were defined based on an annual basis, in the seasons, dry and rainy periods, and during the agricultural calendar of three important crops in the region. Pearson correlation method was applied to identify the effects of atmospheric circulation systems on the values of R, ET0, and W from teleconnection indices for the ten timescales. Significant positive trends of up to + 3.71 mm year−1 for ET0, and negative trends up to -3.48 mm year−1 for W were found. The Atlantic Multidecadal Oscillation (AMO) index and El Niño 1 + 2 (N12) index both showed a correlation with R, ET0 and W only for the annual period. The results indicate the need to adapt the planting times of the main agricultural crops in the region, as well as to reduce water use in irrigated areas, as a strategy for water and food security.